2001
DOI: 10.1002/clc.4960241105
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein diet significantly improves endothelial function and lipid parameters

Abstract: SummaryBackground: Replacement of animal protein with soy protein in the diet is associated with decreased cholesterol levels. However, the effects of soy protein diet on endothelial function are not well known.Hypothesis: The aim of the study was to investigate the effects of soy protein diet on plasma lipids and endothelial function parameters assessed by two different methods.Methods: Twenty hypercholesterolemic, nonsmoker male patients (age 50.1 k 1 1.8 years), with a normal body mass index, were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…Similar controversy exists with respect to vascular reactivity in humans. While some studies have reported no effect or even a reduction in flow-mediated endothelial dilation (Simons et al 2000;Teede et al 2001), others have reported that soy phytoestrogens enhanced flowmediated dilation (Walker et al 2001;Yildirir et al 2001). Collectively, however, there appears to be sufficient support from both animal and human studies to warrant further investigation of the effects of soy and phytoestrogens on blood pressure control.…”
Section: Introductionmentioning
confidence: 85%
“…Similar controversy exists with respect to vascular reactivity in humans. While some studies have reported no effect or even a reduction in flow-mediated endothelial dilation (Simons et al 2000;Teede et al 2001), others have reported that soy phytoestrogens enhanced flowmediated dilation (Walker et al 2001;Yildirir et al 2001). Collectively, however, there appears to be sufficient support from both animal and human studies to warrant further investigation of the effects of soy and phytoestrogens on blood pressure control.…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, Aljada and co-workers (24) showed that a mixed meal high in fat (50% total kcal) significantly (P < 0.05) increased plasma CRP at 3-h post-meal challenges. Although these studies suggest soy may have a minimal effect on inflammatory, fibrinolytic, or coagulation biomarkers, isolated soy protein and isoflavones have been shown to have favorable effects on endothelial function, as assessed with brachial artery reactivity measurements (56)(57)(58). Further, that IL-6 significantly decreased as a function of time during either meal challenge in our study indicates IL-6 is a sensitive biomarker in the postprandial period.…”
Section: Discussionmentioning
confidence: 42%
“…For instance, Jenkins and co-workers (54) reported an increase in IL-6 concentration following a 1-mon soy intervention; other investigations showed no effects of diets high in tofu (52) or isoflavones (53,55) on fibrinogen (52,53,55) or factor VII-c concentrations (53,55). On the other hand, isolated soy protein and isoflavones have favorable effects on endothelial vasoactivity and function, as assessed with brachial artery reactivity measurements (56)(57)(58).…”
mentioning
confidence: 95%
“…Soy isoflavones may improve plasma lipids in normocholesterolemic, postmenopausal women. [48][49][50] Consumption of 25 g/day of isoflavone-containing soy protein is considered part of a heart-healthy diet, when consumed as a substitute for animal products and highly processed foods. 47,48 Daily consumption of soy protein has a favorable impact on vascular reactivity and improves endothelial function regardless of any changes in plasma lipoproteins.…”
Section: Inflammation a Higher Intake Of Dietary Fiber Modulates Sysmentioning
confidence: 99%